Research progress in geophysical exploration of the Antarctic ice sheet - Jinkai An; Song Huang; Xiangyang Chen; Tao Xu; Zhiming Bai (Earthquake Research Advances, 2023)
The Antarctic ice sheet is an important target of Antarctic research. Thickness and structure, including intraice and subice, are closely related to the mass balance of the ice sheet, and play an important role in the study of global sea level and climate change. Subglacial topography is an important basis for studying ice sheet dynamics and ice sheet evolution. This paper briefly reviews the geophysical detection methods and research status of the Antarctic ice sheet: (1) Conventional methods such as ice radar are the main methods for studying the ice sheet today, and passive source seismic methods such as the receiver function method, H/V method and P-wave coda autocorrelation method have good development prospects; (2) the high-resolution (1 ​km) ice thickness and subglacial topographic database BEDMAP2 established based on various data has greatly improved the ability to detect internal isochronous layers, anisotropic layers, and temperature changes within ice and has advanced research on ice sheet evolution; and (3) ice radar, numerical simulation and core drilling are the main methods to study subglacial lakes and sediments. More than 400 subglacial lakes have been confirmed, and more than 12 000 simulation results have been obtained. Research on the Antarctic ice sheet faces enormous challenges and is of great urgency. Aiming at hot issues, such as Antarctic geological evolution, glacial retreat, ice sheet melting and their relationships with global climate change, it is the frontier and trend of future Antarctic ice sheet research to carry out multidisciplinary and multicountry comprehensive geophysical exploration based on the traditional ice radar method combined with passive seismic methods, especially new technologies such as short-period dense array technology, unmanned aerial vehicles and artificial intelligence. This is expected to further promote Antarctic research.